Home-based exercise program in the indeterminate form of Chagas disease (PEDI-CHAGAS study): A study protocol for a randomized clinical trial - Mediano, Mauro F. F.; Ribeiro, Leonardo G.; Silva, Rudson S.; Xavier, Isis G. G.; Vieira, Marcelo C.; Gonçalves, Tatiana R.; Paravidino, Vitor B.; Borges, Juliana P.; Rodrigues Junior, Luiz Fernando; Costa, Henrique S.; Reis, Michel S.; Liporagi-Lopes, Livia C.; et al. (Frontiers in Medicine, 2023)
Background: Chagas disease (CD) is a neglected endemic disease with worldwide impact due to migration. Approximately 50-70% of individuals in the chronic phase of CD present the indeterminate form, characterized by parasitological and/or serological evidence of T.cruzi infection, but without clinical signs and symptoms. Subclinical abnormalities have been reported in indeterminate form of CD, including pro-inflammatory states and alterations in cardiac function, biomarkers and autonomic modulation. Moreover, individuals with CD are usually impacted on their personal and professional life, making social insertion difficult and impacting their mental health and quality of life (QoL). Physical exercise has been acknowledged as an important strategy to prevent and control numerous chronic-degenerative diseases, but unexplored in individuals with the indeterminate form of CD. The PEDI-CHAGAS study (which stands for “Home-Based Exercise Program in the Indeterminate Form of Chagas Disease” in Portuguese) aims to evaluate the effects of a home-based exercise program on physical and mental health outcomes in individuals with indeterminate form of CD. Methods and design: The PEDI-CHAGAS is a two-arm (exercise and control) phase 3 superiority randomized clinical trial including patients with indeterminate form of CD. The exclusion criteria are < 18 years old, evidence of non-Chagasic cardiomyopathy, musculoskeletal or cognitive limitations that preclude the realization of exercise protocol, clinical contraindication for regular exercise, and regular physical exercise (≥1 x per week). Participants will be assessed at baseline, and after three and six months of follow-up. The primary outcome will be QoL. Secondary outcomes will include blood pressure, physical fitness components, nutritional status, fatigability, autonomic modulation, cardiac morphology and function, low back pain, depression and anxiety, stress, sleep quality, medication use and adherence, and biochemical, inflammatory and cardiac biomarkers. Participants in the intervention group will undergo a home-based exercise program whilst those in the control group will receive only general information regarding the benefits of physical activity. Both groups will receive the same general nutritional counseling consisting of general orientations about healthy diets. Conclusion: The findings from the present study may support public health intervention strategies to improve physical and mental health parameters to be implemented more effectively in this population.